Transnationale Reisekonzerne und die Globalisierung der Fremdenverkehrswirtschaft: Konzentrationsprozesse, Struktur- und Raummuster - Vorlaufer, Karl Tillmann (ERDKUNDE, 1993)
The emergence of large transnational enterprises dominating important sections of the tourism industry is a relatively new aspect, determinant and result of the globalization of this industry. The cross-border horizontal and vertical integration, fostered by the creation of a single market within the European Community, takes on a variety of forms ranging from total or partial ownership of firms by acquisition, take-over or mergers to contractual arrangements mainly between travel agencies, tour operators, transportation companies and hotel chains. Based mainly on examples from Germany, this study aims to trace this integration often initiated by tour operators and - to a lesser extent - by airlines. The structural and spatial development patterns and the backward and forward linkages of selected tour operators are analysed. Obviously these enterprises succeeded in building effective marketing organisations based on closely knit spatial networks of travel bureaus either owned and operated by them or connected to them by different contractual arrangements including franchising. Hotel chains and incoming travel agencies in the main tourist destinations are totally or partially owned by the tour operators which became the nuclei of highly integrated corporations. The integration enables these firms to realize a high retention of tourist expenditures and to gain competitive advantages over enterprises only engaged in one branch of the tourism industry. Typical of large German tour operators is that chains of department stores are often the sole or most important shareholders, which in turn are partially owned by major banks. Their stores offer excellent marketing opportunities. German airlines are seldom integrated in tourism corporations dominated by tour operators. On the contrary, in some cases air-carriers interested in decreasing the risk of shortfalls in demand by selling seats to tour operators - try to become direct or indirect shareholders of the giant transnationals. The tourism corporations usually offer standardized services to tourists at reasonable prices. Their market is important and their turnover growing fast. However, the German tourism market is not dominated by oligopolies or even monopolies. On the contrary, based on their flexibility to offer highly specialized tours and services according to the demand of a highly segmented market, small and often tiny tour operators in the German market succeeded in strengthening their position.